Effects of Endotoxemia on Thrombopoiesis in Men - Stohlawetz, Petra; Folman, Claudia C.; von dem Borne, Albert E. G. Kr.; Pernerstorfer, Thomas; Eichler, Hans-Georg; Panzer, Simon; Jilma, Bernd (Thrombosis and Haemostasis, 1999)
Background. Febrile conditions are often associated with increased platelet turnover and refractoriness to platelet transfusions, although several pyrogenic cytokines enhance thrombopoiesis. This study aimed to characterize the effects of experimental human endotoxemia on platelet turnover and thrombopoiesis. Methods. Endotoxin (4 ng/kg) was infused into 30 healthy men to study the regulation of thrombopoiesis in systemic human inflammation. Platelet counts, plasma thrombopoietin (TPO) and glycocalicin levels, and reticulated platelets (RP) were measured to evaluate the effect of acute endotoxemia on thrombopoiesis. Ten subjects received pretreatment with 1000 mg aspirin po. to evaluate possible effects of aspirin on platelet turnover, and ten subjects received paracetamol to control for effects of anti-pyresis. Results. Platelet counts dropped by about 15% (p <0.001) one hour after LPS infusion, began to recover at 24 h, and exceeded baseline values by 8% (CI: 5-12; p <0.001) at 7 days after LPS iv. Reticulated platelet counts increased from 1.62% (CI: 1.24-2.0) to a maximum of 2.39% (CI: 1.81-2.98; p = 0.003) at 6 h. TPO levels increased from baseline values of 10 A.U/ml (CI: 8.8-11.2) to 15.5 A.U/ml (CI: 13.6-17.3) at 24 h (p <0.001), whereas plasma glycocalicin was not changed (p >0.05). The number of circulating platelet-neutrophil aggregates increased more than 100% at 6 h (p <0.001). Neither aspirin nor paracetamol affected changes in any of the parameters measured. Conclusion. Low grade endotoxemia induces a rapid fall of platelet counts, which is followed by an early increase in reticulated platelets and TPO levels but not of glycocalicin levels. Finally peripheral platelet counts increase several days after LPS infusion.